Toward Making Accounting Education Adaptive and Normative. - Campfield, William L. (The Accounting Review, 1970)
Abstract The article examines several factors of the total social environment, which influence educational philosophy for accounting. To be sure, many changes have occurred in American education during the almost two hundred years of our national existence. But most of the significant changes in American education during the 20th Century have dealt with form and techniques rather than with primary purpose. In light of the continuing turmoil on college and university campuses, it is timely to note that more and more educators are questioning the validity of higher education for everyone. It is commonplace that the objectives of accounting education are interrelated and intertwined with the objectives of education for life in general and, in particular, with the objectives of education for involvement in business. One of the revered members of the accounting profession in addressing a group of accounting educators a few years ago pointed out that the greatest educational problem of the profession is that there are almost too many things that accountants should be taught. The concept of standardized curricula and uniform knowledge for the accounting graduate should be abandoned.